COVID-19 in Yemen: How the Drop in Remittances Affected Production, Household Income & Food Systems - Elsabbagh, Dalia; Kurdi, Sikandra; Wiebelt, Manfred (2021)
Dalia Elsabbagh1, Sikandra Kurdi1, and Manfred Wiebelt2 1. International Food Policy Research Institute 2. Kiel Institute for the World Economy Last updated: January 2021